Innovative approaches to the use of flower pollen in sports nutrition - Didukh, Diana; Belinska, Anna (Національний технічний університет "Харківський політехнічний інститут", 2025)
This paper explores innovative bioengineering approaches to enhance the bioavailability of flower pollen in sports nutrition. It analyzes methods such as nanoencapsulation, enzymatic hydrolysis, probiotic fermentation, complexation with adaptogens, and the use of biopolymeric matrices. The proposed approaches improve nutrient absorption by 5–10 times, presenting new opportunities in sports nutrition.
Keywords: innovative approaches; flower pollen; sports nutrition; bioengineering; bioavailability; nanoencapsulation; fermentation; adaptogens